Research on and Application of the Control of Manhole Cover in the Launching Silo Based on Machine Vision Technology. Issue 2 (August 2019) - Yan, Long; Jia, Hai-jie; Ding, Meng-lei; Hou, Dong-dong; Jing, Jun; Zhang, Xiang
Abstract: The manhole cover is an important for the launching device as a whole because its uncovering is vital to the whole switching process. The contact switch is now mainly used to judge whether the manhole cover is in place; however, in this way, the state of the manhole cover cannot be directly observed. In order to make improvement in this regard, this paper adopts machine vision technology to detect the state of the manhole cover and observe the switching process of the manhole cover and detect the in-position signal in real-time by setting a target at a specific position and identifying the target signal using digital image processing technology. Experiment shows that machine vision technology can quickly identify the target signal and directly observe the switching process of the manhole cover.